Family changes: A challenge for edncation in the XXI century - Jadue, Gladys (2003)
The article analyses sorne social factors that increase the possibility of family changes that enlarge children's low achievement and failure, emotional disturbance and behavioral problems at school. Among these factors are the increased life expectancy and geographical mobility, the increased participation of women in the labor force, as well as uniparental families and poverty. It is argued that through the creation of personal development workshops with children from dysfunctional families it is possible to build supporting networks that allow for a good school performance in these children. These workshops should promote understanding of self and others, human interaction and good relationships with family members.